2010
DOI: 10.15288/jsad.2010.71.299
|View full text |Cite
|
Sign up to set email alerts
|

Influence of Heavy Episodic Drinking on the Relation Between Men's Locus of Control and Aggression Toward Intimate Partners

Abstract: ABSTRACT. Objective: This study examined the interactive effects of locus of control and heavy episodic drinking on men's physical assault and sexual coercion against intimate partners. Method: Participants were 151 heterosexual drinking men who completed self-report measures of locus of control, alcohol consumption during the past 12 months, and intimate-partner aggression during the past 12 months. Results: An internal locus of control was associated with a lower frequency of physical assault and sexual coer… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

1
7
0

Year Published

2011
2011
2016
2016

Publication Types

Select...
7

Relationship

4
3

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 56 publications
(65 reference statements)
1
7
0
Order By: Relevance
“…In this way, the protective cognitive power of lower thought suppression may be overridden by alcohol myopia and engender a true “Jekyll and Hyde” effect in which the lower suppressing individual becomes aggressive when intoxicated (Giancola et al, 2010). Overall, these data are consistent with recent findings that alcohol intoxication may override the protective impact of certain cognitive variables (Gallagher & Parrott, 2010) on aggression and provides continued support for the durability of the alcohol myopia effect.…”
Section: Discussionsupporting
confidence: 90%
“…In this way, the protective cognitive power of lower thought suppression may be overridden by alcohol myopia and engender a true “Jekyll and Hyde” effect in which the lower suppressing individual becomes aggressive when intoxicated (Giancola et al, 2010). Overall, these data are consistent with recent findings that alcohol intoxication may override the protective impact of certain cognitive variables (Gallagher & Parrott, 2010) on aggression and provides continued support for the durability of the alcohol myopia effect.…”
Section: Discussionsupporting
confidence: 90%
“…After adjusting for other covariates, however, in our main analysis only alcohol use disorders (among Axis I disorders), increased the likelihood of perpetration, suggesting that the association between Axis I and IPV perpetration may be specific. Alcohol consumption may narrow attentional focus and shift attention toward instigating cues and away from inhibiting cues (Gallagher, & Parrott, ). A previous longitudinal study found a temporal association of alcohol consumption and IPV acts, suggesting that most episodes occur within hours following drinking by a partner (Fals‐Stewart, Golden, & Schumacher, ).…”
Section: Discussionmentioning
confidence: 99%
“…Placebo (i.e., told alcohol, receive no alcohol) and no-alcohol control (i.e., told no alcohol, receive no alcohol) groups were not utilized for two primary reasons. Foremost, two recent studies found that a cognitive distraction intervention manipulation failed to reduce aggression in men who received placebo control beverages (Giancola & Corman, 2007) or highly provoked men who received no-alcohol control beverages (Gallagher & Parrott, 2010). However, the cognitive distraction intervention manipulation significantly reduced aggression among intoxicated men.…”
Section: Methodsmentioning
confidence: 99%